2020
DOI: 10.1016/j.irle.2020.105909
|View full text |Cite
|
Sign up to set email alerts
|

Exploring dissent in the Supreme Court of Argentina

Abstract: When dissents are allowed, judges must decide whether or when to write them. While the main insights of rational dissent theory have been documented and corroborated in several empirical studies, there has been much less evidence testing on how different types of dissent may affect the likelihood of dissent. Particularly, dissents in more salient cases, or more forceful dissents, may have stronger legal effects than dissents appearing in less relevant cases or very narrowly construed dissents. Our article aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…Although results in Argentina's Supreme Court showed that more important cases had a lower likelihood of carrying a dissenting opinion, when analyzing the category of "reasoned dissents", they found that majority decisions carrying dissents tend to be longer and those were allocated in important cases. In Muro et al (2020).…”
Section: Judicial Dissentmentioning
confidence: 99%
“…Although results in Argentina's Supreme Court showed that more important cases had a lower likelihood of carrying a dissenting opinion, when analyzing the category of "reasoned dissents", they found that majority decisions carrying dissents tend to be longer and those were allocated in important cases. In Muro et al (2020).…”
Section: Judicial Dissentmentioning
confidence: 99%
“…No obstante, este tipo de normas requieren la intervención, de forma más intensa, de un tribunal constitucional, hecho que puede provocar la disminución en la emisión de opiniones disidentes. En resumen, la teoría principal-agente es compleja y no proporciona respuestas rotundas 38 . puede resultar complejo identificar la diferencia entre el voto informal (manifestar el desacuerdo de forma oral) y el voto formal (formular la opinión disidente por escrito).…”
unclassified